Answer:
75:80 OR 15:16
Step-by-step explanation:
The answer is letter d) 3
You would subitute -2 for x in the equation
f(-2)=x^2-6
PEMDAS so exonents
-2^2-6
negative times a negative= positive
4-6
f(-2)=-2
f(x) means that you subsitute x for x in the equation exg
f(1)=x+2 means f(1)=1+2
f(4)=x+2 means f(4)=4+2
Answer:
Bjgxhjhfy bună bună bună bună bună bună bună bună ziua domnule profesor de matematica și nu
Answer:
a. 1 triangle
Step-by-step explanation:
measure line QS=8.cm measure 85°on side Q